Spontaniczność jako narzędzie perswazji w zachowaniach formulicznych (na materiale wybranych protokołów cechowych z XVIII w.) = Spontaneity as a tool of persuasion in formulaic behaviour (with the material of selected guild protocols of the eighteenth century) - Pałucka-Czerniak, Iwona (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article describes the question of persuasion, manifested in the spontaneous, emotional and evaluative writings, present in guild protocols of Krakow brewers from the eighteenth century. Persuasiveness of the writings in the guild book aimed primarily at building the authority of the community and its representative and documenting the merits of the complaint ascended to a higher instance.
Keywords: spontaniczność; perswazja; protokoły cechowe; autorytet; 18 w.; spontaneity; persuasion; guild protocols; authority